PERSUASI PENGURANGAN PENGGUNAAN KANTONG PLASTIK MELALUI NARASI DAN PERSEPSI RESIKO - Gumgum Gumelar (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
Studies on the effect of persuasion message in a proenvironmental behavior context have been focused on the utilization of argumentative massage type to ensure changes in individual’s behavior. The purpose of this research is to testing whether persuasion narration on type message, based on the risk in mediation by drifting, can reduce the use of plastic bag. This research method used an experimental method by giving manipulation in reading the material form and fill three instruments for 167 respondents. The result suggests that health risk framing messages were more likely increase proenvironmental behaviors in use reduction of plastic bags compares to environmentalrisk framing messages. This effect appears due to the historical transportation process. This research contributes to literacy of the community of reducing the use of a plastic bag to improve environmentally friendly behavior.